Policy effects on class-gender employment intersections - Lynn Prince Cooke (Luxembourg Income Study (LIS), 2009)
This project explored how the sociopolitical context maps current class-gender intersections in relative employment equality in Australia, East and West Germany, Spain, the United Kingdom, and the United States. The countries were selected based on their diverse policy equality logics codified in initial welfare state provisions. Pooled and individual-country analyses of wave 5.2 of the Luxembourg Income Study revealed gender differences in the impact of individual factors on work hours and wages, as well as national differences controlling for individual characteristics. Two findings bear particular note. First, the differences in relative gender earnings inequality across the class distribution in Australia and West Germany underline that class equality policies do not ensure greater class equality for all social groups. Second, the UK and US results indicate that liberal market forces do not ensure women's greater investment in education and work hours will achieve economic equality with men. As women's 'human capital' increases, men's returns to their own increase such that gender employment equality becomes a moving target.
Keywords: 330; Arbeitsmarktsegmentation; Weibliche Arbeitskräfte; Geschlechterdiskriminierung; Australien; Deutschland; Großbritannien; Spanien; USA